The Influence of Professional Competence on High School Teacher Performance in the Covid-19 Era (Pengaruh Kompetensi Profesional Tehadap Kinerja Guru SMA di Era Covid-19) - Rum, Jalaluddin; Irwan, Irwan (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
This research aims to examine the influence of professional competence on teacher performance in Konawe Islands Regency. This research is quantitative research with correlational techniques, the sample size is 69 people. The data analysis used is simple regression analysis. The research results show that there is a significant influence between professional competence and the performance of high school teachers in Konawe Islands Regency. This means that the professional competence and performance of high school teachers in the Konawe Islands Regency are getting better. These results are also strengthened by the correlation test which shows that there is a significant relationship between professional competence and the performance of high school teachers in Konawe Islands Regency. The professional competence of high school teachers in Konawe Islands Regency is included in the good category. This means that high school teachers have high teaching quality and carry out their duties with full responsibility. The performance of high school teachers based on research results is also classified as good, which means that the performance of high school teachers in planning, implementing and assessing and evaluating learning activities has been carried out well.Keywords: Professional Competence, High School, Teacher Performance